2020
DOI: 10.9770/jssi.2020.10.1(4)
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Reporting Quality Assessment

Abstract: This research aims to investigate the integrated reporting (IR)quality on European firms and whether there is an improvement on (IR)quality from 2016 to 2017. Using 63 firms in the period of 2016 and 2017, the content analysis method then applied to evaluate the quality of 126 integrated reports. This results then used to investigate whether there is an improvement of the integrated reporting quality from 2016 to 2017. The research findings show that the European firms, on average, published a moderate quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In general, empirical research on disclosures about the BM can be divided into two main groups, the first, raising the problem of compliance of BM disclosures with the <IR> Framework proposed by IIRC (Eccles et al, 2015;Bek-Gaik and Rymkiewicz, 2016;Walińska et al, 2015;Albertini, 2019;Malola and Maroun, 2019), and the second group aimed at assessing the quality of disclosed information on the BM (Lai et al, 2013;Eccles and Krzus, 2014;Bagnoli and Redigolo, 2015;Bini et al, 2016;Melloni et al, 2016;Kiliç and Kuzey, 2018;Lai et al, 2018;Pistoni et al, 2018;Bezverkhyi et al, 2019;Gerwanski et al, 2019;Sukhari and de Villiers, 2019;Agustia et al, 2020;Songini et al, 2020;Bek-Gaik and Surowiec, 2020;Al Amosh and Mansor, 2021;Iatridis et al, 2021;Songini et al, 2021).…”
Section: Business Model In Integrated Reports -Results Of Literature ...mentioning
confidence: 99%
“…In general, empirical research on disclosures about the BM can be divided into two main groups, the first, raising the problem of compliance of BM disclosures with the <IR> Framework proposed by IIRC (Eccles et al, 2015;Bek-Gaik and Rymkiewicz, 2016;Walińska et al, 2015;Albertini, 2019;Malola and Maroun, 2019), and the second group aimed at assessing the quality of disclosed information on the BM (Lai et al, 2013;Eccles and Krzus, 2014;Bagnoli and Redigolo, 2015;Bini et al, 2016;Melloni et al, 2016;Kiliç and Kuzey, 2018;Lai et al, 2018;Pistoni et al, 2018;Bezverkhyi et al, 2019;Gerwanski et al, 2019;Sukhari and de Villiers, 2019;Agustia et al, 2020;Songini et al, 2020;Bek-Gaik and Surowiec, 2020;Al Amosh and Mansor, 2021;Iatridis et al, 2021;Songini et al, 2021).…”
Section: Business Model In Integrated Reports -Results Of Literature ...mentioning
confidence: 99%
“…The research on the quality of integrated reporting was conducted on the example of different regions. Agustia et al (2020) found that the integrated reports published by European firms show moderate quality, however they observed an partial improvement in integrated reporting quality over time, especially for readibility and clarity of reports. Al Amos and Mansor (2021) examined the current state of integrated reporting quality in a developing country and indicated significant variations in the current practice, where the high level of disclosure presented only two reporting elementsrisks and opportunities, and the basis of preparation and presentation, while the disappointing level of disclosure showed such reporting elements as governance and outlook.…”
Section: Empirical Research On Forward-looking Disclosures In Integra...mentioning
confidence: 93%
“…• The use of management accounting tools in the process of preparing an integrated report (Massingham, 2019). • Quality of disclosures in in integrated reporting (e.g., Pistoni et al, 2018;Kiliç and Kuzey, 2018;Bezverkhyi et al, 2019;Gerwanski et al, 2019;Agustia et al, 2020;Songini et al, 2020;Al Amos and Mansor, 2021;Iatridis et al, 2021;Songini et al, 2021). • Analysis of the information content of integrated reports and comparison of the structure of integrated reports with the framework of integrated reporting (e.g., Eccles and Krzus, 2014;Chersan, 2015;Eccles et al, 2015;Jinga and Dumitru, 2015;Albertini, 2019;Malola and Maroun, 2019).…”
Section: Empirical Research On Forward-looking Disclosures In Integra...mentioning
confidence: 99%
“…Companies are progressively aligning their reports with IR requirements as IR practices take shape. The level and quality of IR have significantly improved over time, according to the findings of Ahmed Haji and Anifowose (2016), Pistoni et al (2018) and Agustia et al (2020), while some concepts still need to be established. Therefore, future research could explore IR practice longitudinally, considering there has been a decade of IR implementation.…”
Section: Future Empirical Directionsmentioning
confidence: 99%
“…According to this theory, if IR forces companies to disclose proprietary information, the company’s value will decrease because IR disclosures become expensive. Companies will limit voluntary disclosure because the dissemination of strategic information can provide advantages for competitors (Lee and Yeo, 2016; Pistoni et al , 2018; Agustia et al , 2020).…”
Section: Theoretical Lensesmentioning
confidence: 99%